The ups and downs of growth hormone secretagogue receptor signaling. (2nd March 2021) - Cornejo, María P.; Mustafá, Emilio R.; Cassano, Daniela; Banères, Jean‐Louis; Raingo, Jesica; Perello, Mario
Abstract : The growth hormone secretagogue receptor (GHSR) has emerged as one of the most fascinating molecules from the perspective of neuroendocrine control. GHSR is mainly expressed in the pituitary and the brain, and plays key roles regulating not only growth hormone secretion but also food intake, adiposity, body weight, glucose homeostasis and other complex functions. Quite atypically, GHSR signaling displays a basal constitutive activity that can be up‐ or downregulated by two digestive system‐derived hormones: the octanoylated‐peptide ghrelin and the liver‐expressed antimicrobial peptide 2 (LEAP2), which was recently recognized as an endogenous GHSR ligand. The existence of two ligands with contrary actions indicates that GHSR activity can be tightly regulated and that the receptor displays the capability to integrate such opposing inputs in order to provide a balanced intracellular signal. This article provides a summary of the current understanding of the biology of ghrelin, LEAP2 and GHSR and discusses the reconceptualization of the cellular and physiological implications of the ligand‐regulated GHSR signaling, based on the latest findings. Abstract : The growth hormone secretagogue receptor (GHSR) is a fascinating molecule that controls numerous neuroendocrine functions and behaviors. GHSR activity is up‐ and downregulated by two digestive system‐derived peptides, ghrelin and liver‐expressed antimicrobial peptide 2 (LEAP2), respectively, that, in turn, integrate different types of metabolic, autonomic, and endocrine signals. This article summarizes the biology of ghrelin, LEAP2 and GHSR and discusses the cellular and physiological implications of GHSR signaling.